Pemasaran Online: Keputusan Konsumen Dipengaruhi Oleh Diskon dan Ulasan Online - Shafira, Azzahra; Tuti, Meylani (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2024)
Recent developments have accelerated the shift in consumer behavior towards online shopping, as they can access online reviews from previous customers, which provide additional information and influence brand trust. Apart from that, there are also regular discount offers.This research aims to find out how online customer reviews and discount prices through brand trust influence purchasing decisions. The population in this study was Migli.id consumers who made online purchases in November and December 2023. Using accidental sampling, 226 samples were obtained. The analysis method was carried out using the Structure Equation Model and using Smart PLS 3. The results show that all independent variables, namely online customer reviews and discount prices, have a good influence on brand trust and purchasing decisions. The managerial implication of this research is that trust is an important thing that sellers must strive for in marketing their products because that is what will encourage consumers to make purchases.